The feminist avant-garde in American poetry - Frost, Elisabeth A. (Elisabeth Ann), 1963- (Book collections on Project MUSE., 2003)
The Feminist Avant-Garde in American Poetry offers a historical and theoretical account of avant-garde women poets in America from the 1910s through the 1990s and asserts an alternative tradition to the predominantly male-dominated avant-garde movements. Elisabeth Frost argues that this alternative lineage distinguishes itself by its feminism and its ambivalence toward existing avant-garde projects; she also thoroughly explores feminist avant-garde poets' debts and contributions to their male counterparts. --